Performance of Fe y Alegría High School Students in Colombia : Is it a Matter of Fe (Faith) or Alegría (Joy)? - Osorio, Juan Carlos Parra (2012)
Fe y Alegria is a catholic network of schools that started operations in Colombia in 1971, and in 2009 served more than 72,000 students in 61 schools. This paper assesses the performance of Fe y Alegria secondary schools in Colombia using test scores for Spanish and mathematics, as well as detailed information on the characteristics of the household to which students belong. Simple statistics suggest that Fe y Alegria schools perform worse than other schools for all years in the sample. However, Fe y Alegria schools also cater to poorer students who come from disadvantaged backgrounds. Once controls are included for student background, Fe y Alegria schools actually often perform as well and in some cases better than other schools for mathematics and Spanish, thus partially reversing the previous finding.